TREATMENT OF PURULENT-NECROTIC COMPLICATIONS OF SOFT TISSUES IN DIABETES MELLITUS - Abdullaev S.A. (Scholar Express Journals, 2025)
One of the common complications of diabetes mellitus (DM) is damage to the blood vessels of the human body, leading to the development of diabetic foot. Literature data and daily practical observation show an increase in the incidence of diabetic foot (30-70%), which increases the urgency of treating this disease. The article contains data on the results of surgical treatment of 151 patients with diabetes mellitus complicated by diabetic foot and purulent-necrotic soft tissue inflammations. Our work presents the basic principles of treatment of purulent-necrotic complications of diabetes mellitus. The effectiveness of topical application of Acerbin solution and twostage surgical tactics in the complex surgical treatment of purulent-necrotic complications of diabetes mellitus has been proven.
Keywords: diabetes mellitus; purulent-necrotic complications